2011
DOI: 10.1186/1471-2105-12-398
|View full text |Cite
|
Sign up to set email alerts
|

SCOWLP update: 3D classification of protein-protein, -peptide, -saccharide and -nucleic acid interactions, and structure-based binding inferences across folds

Abstract: BackgroundProtein interactions are essential for coordinating cellular functions. Proteomic studies have already elucidated a huge amount of protein-protein interactions that require detailed functional analysis. Understanding the structural basis of each individual interaction through their structural determination is necessary, yet an unfeasible task. Therefore, computational tools able to predict protein binding regions and recognition modes are required to rationalize putative molecular functions for prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Protein Definition, Expression and Purification All human SH3 domain sequences predicted by InterProScan (Quevillon et al, 2005) (Perrakis et al, 1997) http://www.embl-hamburg.de/ARP/ MolProbity (Chen et al, 2010) http://molprobity.biochem.duke.edu/ Buccaneer (Cowtan, 2006) http://www.ccp4.ac.uk/ Refmac (Murshudov et al, 2011) http://www.ccp4.ac.uk/ Coot (Emsley et al, 2010) http://www2.mrc-lmb.cam.ac.uk/Personal/ pemsley/coot/ MUSI (Kim et al, 2012) http://www.kimlab.org/software/musi InterProScan (Quevillon et al, 2005) http://www.ebi.ac.uk/interpro/search/ sequence-search PROSITE (Sigrist et al, 2013) http://prosite.expasy.org/ Superfamily (Oates et al, 2015) http://supfam.org/SUPERFAMILY/ Pfam (Punta et al, 2012) http://pfam.xfam.org/ SMART (Letunic et al, 2015) http://smart.embl-heidelberg.de/ Mafft (Katoh et al, 2002) http://mafft.cbrc.jp/alignment/software/ 3DID (Stein et al, 2010) http://3did.irbbarcelona.org/ SCOWLP (Teyra et al, 2011) http://projects.biotec.tu-dresden.de/ scowlp/…”
Section: Star+methods Key Resources Table Contact For Reagent and Resmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein Definition, Expression and Purification All human SH3 domain sequences predicted by InterProScan (Quevillon et al, 2005) (Perrakis et al, 1997) http://www.embl-hamburg.de/ARP/ MolProbity (Chen et al, 2010) http://molprobity.biochem.duke.edu/ Buccaneer (Cowtan, 2006) http://www.ccp4.ac.uk/ Refmac (Murshudov et al, 2011) http://www.ccp4.ac.uk/ Coot (Emsley et al, 2010) http://www2.mrc-lmb.cam.ac.uk/Personal/ pemsley/coot/ MUSI (Kim et al, 2012) http://www.kimlab.org/software/musi InterProScan (Quevillon et al, 2005) http://www.ebi.ac.uk/interpro/search/ sequence-search PROSITE (Sigrist et al, 2013) http://prosite.expasy.org/ Superfamily (Oates et al, 2015) http://supfam.org/SUPERFAMILY/ Pfam (Punta et al, 2012) http://pfam.xfam.org/ SMART (Letunic et al, 2015) http://smart.embl-heidelberg.de/ Mafft (Katoh et al, 2002) http://mafft.cbrc.jp/alignment/software/ 3DID (Stein et al, 2010) http://3did.irbbarcelona.org/ SCOWLP (Teyra et al, 2011) http://projects.biotec.tu-dresden.de/ scowlp/…”
Section: Star+methods Key Resources Table Contact For Reagent and Resmentioning
confidence: 99%
“…This sequence alignment was used to define the standard SH3 domain numbering scheme. In addition, 3DID (Stein et al, 2010) and SCOWLP database (Teyra et al, 2011) were used to automatically extract all the SH3 domain-peptide complexes in the PDB repository (Table S3). In total, we identified 484 SH3 domain-containing PDB files, and 91 of these were for SH3 domains binding to a polypeptide chain.…”
Section: Analysis Of Sh3 Domains and Complexesmentioning
confidence: 99%
“…For some entries, the PDB provides additional biological assemblies derived from the Protein Interfaces, Surfaces and Assemblies (PISA) 4 server from the EBI that are predicted to be stable in solution based on calculations of thermodynamic stability of the complexes. Several servers analyze interfaces in either the asymmetric units and/or the deposited biological assemblies of PDB entries [6][7][8][9][10][11] , and some are intended to predict which interfaces may be biologically relevant by measuring conservation scores and physical features and using machine learning predictors [12][13][14] . Interactions with peptides, nucleic acids, and ligands have also been analyzed and presented in several webservers and databases 9,[15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are annotated 179 classes of literature‐curated motifs that are interacting to 87 distinct Pfam domains. However, analysis of the PDB repository has shown that the peptide‐binding domain families are much more abundant [80,81]. For example, PepX database currently contains 119 Pfam domains structurally solved in complex to peptides, suggesting that the biologically relevant peptide‐binding domains might be larger.…”
Section: Future Perspectivesmentioning
confidence: 99%